1996
DOI: 10.1021/bi9528560
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Mutagenesis of Aspartic Acid Residues in the Putative Phosphoribosyl Diphosphate Binding Site of Escherichia coli Phosphoribosyl Diphosphate Synthetase on Metal Ion Specificity and Ribose 5-Phosphate Binding

Abstract: The three conserved aspartic acid residues of the 5-phospho-D-ribosyl alpha-1-diphosphate binding site (213-GRDCVLVDDMIDTGGT-228) of Escherichia coli phosphoribosyl diphosphate synthetase were studied by analysis of the mutant enzymes D220E, D220F, D221A, D224A, and D224S. The mutant enzymes showed an increase in KM for ribose 5-phosphate in the presence of at least one of the divalent metal ions Mg2+, Mn2+, Co2+, or Cd2+, with the most dramatic changes revealed by the D220E and D220F enzymes in the presence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…However, according to the crystal structure of B. subtilis PRPP synthase, the true substrate of the enzyme is the ␣,␤,␥-tridentate complex of MgATP, which is consistent with the MG2 site described above. Additionally, analysis of E. coli PRPP synthase with an altered ribose 5-phosphate-binding site (Asp220Glu, Asp220Phe, and Asp221Ala) revealed that the effects on the values for the apparent maximal velocity (V app ) and K m for ribose 5-phosphate were dependent on the divalent cation present, suggesting that the binding of ribose 5-phosphate also occurs via interaction with Mg 2ϩ (61), which is consistent with the MG1 site described above. The crystal structure, furthermore, completes nuclear magnetic resonance analyses that attempted to elucidate the conformation of ATP at the active site of S. enterica PRPP synthase.…”
Section: Class I Prpp Synthasessupporting
confidence: 74%
See 1 more Smart Citation
“…However, according to the crystal structure of B. subtilis PRPP synthase, the true substrate of the enzyme is the ␣,␤,␥-tridentate complex of MgATP, which is consistent with the MG2 site described above. Additionally, analysis of E. coli PRPP synthase with an altered ribose 5-phosphate-binding site (Asp220Glu, Asp220Phe, and Asp221Ala) revealed that the effects on the values for the apparent maximal velocity (V app ) and K m for ribose 5-phosphate were dependent on the divalent cation present, suggesting that the binding of ribose 5-phosphate also occurs via interaction with Mg 2ϩ (61), which is consistent with the MG1 site described above. The crystal structure, furthermore, completes nuclear magnetic resonance analyses that attempted to elucidate the conformation of ATP at the active site of S. enterica PRPP synthase.…”
Section: Class I Prpp Synthasessupporting
confidence: 74%
“…In addition, an overwhelming volume of research data has shown that an additional so-called free Mg 2ϩ is required for activity, because maximal activity is only obtained when Mg 2ϩ is added to the reaction mixture in excess of the MgATP concentration for both bacterial (35,45,(55)(56)(57)(58) and mammalian (59,60) PRPP synthases. Furthermore, most PRPP synthases may accept other divalent metal ions in place of Mg 2ϩ , and thus Mg 2ϩ may be regarded as a pseudosubstrate (45,56,58,61). In contrast, Ca 2ϩ is an inhibitor of PRPP synthase activity, even in the presence of Mg 2ϩ (45).…”
Section: Class I Prpp Synthasesmentioning
confidence: 99%
“…The enzymes of class I are activated by phosphate ions and are allosterically inhibited by the ribonucleoside diphosphate ADP. In fact kinetic analysis has revealed that ADP and phosphate ion compete for binding to a common regulatory site of E. coli PRPP synthase, 17 whereas crystallographic analysis has revealed that a sulphate ion, an analogue of a phosphate ion, occupys a position similar to the b-phosphorus of a,b-methylene ADP in a crystal structure of B. subtilis PRPP synthase in complex with sulphate ion. 13 23,24 These enzymes use ATP and in some cases also dATP as diphosphoryl donor.…”
Section: Discussionmentioning
confidence: 99%
“…[8-14 C]ADP was from Amersham Pharmacia Biotech. E. coli PRPP synthase was purified as described previously (11,27) and had a specific activity of approximately 150 mol min Ϫ1 mg Ϫ1 when assayed in the presence of 2 mM ATP, 5 mM Rib-5-P, 5 mM MgCl 2 as described below. The protein concentration was determined by the bicinchoninic acid procedure (28) with reagents provided by Pierce and with bovine serum albumin as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…Assay of PRPP Synthase Activity-The 32 P transfer assay was performed at 37°C in 55 mM triethanolamine, pH 8.0, as described previously (11,27), except that enzyme was diluted in 2 mM ATP, 10 mM MgCl 2 , 50 mM triethanolamine, pH 8.0, bovine serum albumin (1 mg ml…”
Section: Methodsmentioning
confidence: 99%